Photosynthetic Bacteria: Light-Responsive Biomaterials for Anti-Tumor Photodynamic Therapy - Jiang Y (International Journal of Nanomedicine)
Yuan Jiang Department of Rehabilitation Medicine, School of Clinical Medicine and The First Affiliated Hospital of Chengdu Medical College, Chengdu, Sichuan, People’s Republic of ChinaCorrespondence: Yuan Jiang, Email 85741920@qq.comAbstract: Photodynamic therapy (PDT) is a promising noninvasive tumor treatment modality that relies on generating reactive oxygen species (ROS) and requires an adequate oxygen supply to the target tissue. However, hypoxia is a common feature of solid tumors and profoundly restricts the anti-tumor efficacy of PDT. In recent years, scholars have focused on exploring nanomaterial-based strategies for oxygen supplementation and integrating non-oxygen-consuming treatment approaches to overcome the hypoxic limitations of PDT. Some scholars have harnessed the photosynthetic oxygen production of cyanobacteria under light irradiation to overcome tumor hypoxia and engineered them as carriers of photosensitizers instead of inorganic nanomaterials, resulting in photosynthetic bacteria (PSB) attracting significant attention. Recent studies have shown that light-triggered PSB can exhibit additional properties, such as photosynthetic hydrogen production, ROS generation, and photothermal conversion, facilitating their use as promising light-responsive biomaterials for enhancing the anti-tumor efficacy of PDT. Therefore, understanding PSB can provide new insights and ideas for future research. This review mainly introduces the characteristics of PSB and recent research on light-triggered PSB in anti-tumor PDT to enrich our knowledge in this area. Finally, the challenges and prospects of using PSB to enhance the anti-tumor efficacy of PDT were also discussed.Keywords: photosynthetic bacteria, PDT, hypoxia, cyanobacteria, purple bacteria, PTT